2014
DOI: 10.1111/1348-0421.12173
|View full text |Cite
|
Sign up to set email alerts
|

Association between aggregative adherence fimbriae types including putative new variants and virulence‐related genes and clump formation amongaggR‐positiveEscherichia colistrains isolated in Thailand and Japan

Abstract: Enteroaggregative Escherichia coli (EAggEC) are an important cause of diarrhea. Four types of AAF have been identified; however, their prevalence and association with virulence properties remain unclear. E. coli strains carrying the aggR gene as EAggEC that were isolated in Japan and Thailand (n ¼ 90) were examined for AAF subunit genes, two toxin genes (pet/astA), and clump formation. The most prevalent AAF gene was hdaA (28%), followed by aafA (20%), aggA (12%), and agg3A (4%), as well as a putative new AAF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
(37 reference statements)
2
9
1
Order By: Relevance
“…In fact, EAEC O126:H27 caused an outbreak in Shizuoka, Japan, in 2005 (5). Ito et al also recently reported that these three serotypes are frequently found in Japan (45). However, these three serotypes have not been reported to be prevalent in other countries (15,24,46,47), suggesting that the dominant EAEC serotypes differ geographically.…”
Section: Discussionmentioning
confidence: 95%
“…In fact, EAEC O126:H27 caused an outbreak in Shizuoka, Japan, in 2005 (5). Ito et al also recently reported that these three serotypes are frequently found in Japan (45). However, these three serotypes have not been reported to be prevalent in other countries (15,24,46,47), suggesting that the dominant EAEC serotypes differ geographically.…”
Section: Discussionmentioning
confidence: 95%
“…Bacterial culture (BC): BC was performed by directand enrichment-culture techniques as described previously (16)(17)(18). For isolation of diarrheagenic E. coli, we screened 5-40 colonies grown on Chromocult coliform agar (Merck, Darmstadt, Germany) using PCR as described (19). If C. jejuni and astA gene-positive E. coli were detected with RFBS24 ver.5 but not with BC, isolation of C. jejuni was performed using modified charcoal-cefoperazone-deoxycholate (CCDA) agar (Oxoid, Basingstoke, UK) followed by enrichment culture at 42 C for 24 h in Preston Campylobacter selective enrichment broth (Oxoid).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PCR results revealed that 5 AAF-negative OUT:H10 strains harbored the O99 antigen. Many OUT EAEC strains have been reported domestically and overseas (28,29 (22,30,31). Therefore, the prevalence of O:H types is likely to vary among countries.…”
Section: Discussionmentioning
confidence: 99%